2009
DOI: 10.1111/j.1746-1561.2009.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Internet Risk Behaviors in a Middle School Student Population

Abstract: Findings suggest that middle school students who are early adolescents are beginning risky behaviors on the Internet. Risk-taking behavior is not unique to adolescents, but the consequences can be detrimental to their development. Educators, clinicians, health care providers, and other professionals need to be informed of Internet behaviors in order to assess for children at risk, to make referrals, intervene, and to educate parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 15 publications
1
43
0
4
Order By: Relevance
“…Our study has also shown that older adolescents engage in risky online behaviours more often than younger ones. Similar results were found in Dowell, Burgess, & Cavanaugh (2009) study: in the later adolescence students are likely to share their personal information, engage in cyberbullying, talk about sexual things and visit sex-related web pages. As Smahel, Brown & Blinka (2012) suggest, at the later adolescence teens are in the lack of social contacts, thus, the majority of the time they spend being alone what draws them up to use the Internet and engage in risky behaviours.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Our study has also shown that older adolescents engage in risky online behaviours more often than younger ones. Similar results were found in Dowell, Burgess, & Cavanaugh (2009) study: in the later adolescence students are likely to share their personal information, engage in cyberbullying, talk about sexual things and visit sex-related web pages. As Smahel, Brown & Blinka (2012) suggest, at the later adolescence teens are in the lack of social contacts, thus, the majority of the time they spend being alone what draws them up to use the Internet and engage in risky behaviours.…”
Section: Discussionsupporting
confidence: 76%
“…It is also related to the teenagers' tendency to experiment with one's identity and to discover the surroundings (Dowell, Burgess, & Cavanaugh, 2009). The usage of the Internet here plays an important role as a longer time spent on the Internet is positively related to adolescents' risky online behaviour (Wach et al, 2015).…”
Section: Students' Engagement In Risky Online Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…One study found that females are online more frequently for socializing purposes, in comparison to males, who go online more frequently to play games (Dowell et al, 2009). In another study conducted by (Juvonen and Gross, 2008) results showed that girls were significantly more likely to be users of email, profile sites, blogs and cell phones in comparison to boys.…”
Section: Introductionmentioning
confidence: 93%